Comparison of lente insulin and NPH insulin therapy for the treatment of newly diagnosed diabetic dogs: a randomised study. (1st September 2018) - Fracassi, Federico; Linari, Guido; Del Baldo, Francesca; Di Cunzolo, Antonella; D'Angelo, Simona; Malerba, Eleonora; Carotenuto, Gaia; Bonfanti, Ugo; Corradini, Sara
Abstract : Clinical studies that compare lente insulin and neutral protamine Hagedorn (NPH) insulin in diabetic dogs are lacking. This is a prospective, randomised, controlled clinical study aimed to compare the efficacy and safety of lente insulin and NPH insulin in diabetic dogs. Thirty client‐owned, newly diagnosed diabetic dogs were included. Animals were randomised into two groups and received lente insulin or NPH insulin administered every 12 hours. Follow‐up re‐evaluations were done at 1, 2, 4, 6, 8 and 12 weeks. At each re‐evaluation, a physical exam, blood glucose curve, and serum fructosamine concentrations were performed. At the end of the study, the median insulin dose per injection was 0.61 U/kg (range, 0.34–0.92 U/kg) and 0.49 U/kg (range, 0.23–0.68 U/kg) in the lente and NPH groups, respectively. There was a significant improvement of polyuria and polydipsia and glucose concentrations in both groups. At the end of the study, the glycaemic control was considered good in 9/15 (60 per cent) and 11/15 (73 per cent) in the lente and NPH groups, respectively. These differences were not significant. Lente insulin and NPH insulin were similarly effective in the treatment of dogs with diabetes mellitus.